Intravenous Thrombolysis for Stroke Recurring Within 3 Months From the Previous Event. Issue 11 (November 2015) - Karlinski, Michal; Kobayashi, Adam; Czlonkowska, Anna; Mikulik, Robert; Vaclavik, Daniel; Brozman, Miroslav; Gdovinova, Zuzana; Švigelj, Viktor; Csiba, Laszlo; Fekete, Klara; Kõrv, Janika; Demarin, Vida; et al.
Abstract : Background and Purpose—: According to the European license, alteplase can be given no sooner than 3 months after previous stroke. However, it is not known whether past history of stroke influences the effect of treatment. Our aim was to evaluate safety and functional outcome after intravenous thrombolysis administered in everyday practice to patients with previous stroke ⩽3 months compared with those with first-ever stroke. Methods—: We analyzed consecutive cases treated with alteplase between October 2003 and July 2014 contributed to the Safe Implementation of Thrombolysis for Stroke–Eastern Europe registry from 12 countries. Odds ratios were calculated using unadjusted and adjusted logistic regression. Results—: Of 13 007 patients, 11 221 (86%) had no history of stroke and 249 (2%) experienced previous stroke ⩽3 months before admission. Patients with previous stroke ⩽3 months had a higher proportion of hypertension and hyperlipidemia. There were no significant differences in outcome, including symptomatic intracerebral hemorrhage according to European Cooperative Acute Stroke Study (unadjusted odds ratio 1.27, 95% confidence interval: 0.74–2.15), and being alive and independent at 3 months (odds ratio 0.81, 95% confidence interval: 0.61–1.09). Conclusions—: Patients currently treated with alteplase, despite a history of previous stroke ⩽3 months, do not seem to achieve worse outcome than those with first-ever stroke. Although careful patient selection was probably of major importance, our findings provide reassurance that this group of patients may safely benefit from thrombolysis and should not be arbitrarily excluded as a whole. Further studies are needed to identify the shortest safe time lapse from the previous event to treatment with alteplase. Abstract : Supplemental Digital Content is available in the text.